Impact of Lifestyle Interventions on Quality and Consumption of Hyper-Palatable Foods Within Gestational Diets: Single-Goal vs Multiple-Goal. (29th May 2020) - Hand, Lauren; Hoover, Anna; Herman, Amy; Comfort, Lucas; Fazzino, Tera; Sullivan, Debra; Hull, Holly
Abstract: Objectives: Examine the impact of a multiple-goal (MG) vs single-goal (SG) lifestyle interventions on gestational diet quality and hyper-palatable food consumption. Methods: Pregnant women were randomized in two pilot trials to MG ( n = 21) or SG ( n = 16) vs usual care (UC; combined trials, n = 18). The 18-week MG intervention included lifestyle modifications, and the 12-week SG intervention focused only on increasing fiber (≥30 g/day). Interventions included weekly instruction by a registered dietitian, and primary aims were appropriate weight gain. Diet recalls were performed at baseline and study end. Diet quality was scored with three versions of the alternative healthy eating index, including adaptations for pregnancy (AHEI 2010, AHEI-P, and AHEI-P 2010). Foods were classified as hyper-palatable based on fat, carbohydrate, sugar, and sodium content using previously defined criteria, and reported as percentage of total calories (%HPF). One-way ANOVA, paired t-tests, and Pearson's correlations were performed. Results: At baseline, no between group differences for diet quality were found. By the end of the study, all diet quality scores increased for SG ( P < 0.009) and two increased for MG (AHEI 2010 & AHEI-P-2010, P < 0.041). UC diet quality remained unchanged ( P > 0.05). At baseline, %HPF was different between groups (MG > UC > SG, 82%, 57%, and 26%, respectively; P < 0.001). By study end, UC and SG increased %HPF ( P < 0.033), while MG remained unchanged ( P > 0.05), leaving MG and SG similar in %HPF (80% & 74%, respectively) and higher than UC (65%, P = 0.024). The %HPF was negatively correlated with all diet quality scores at baseline ( r = −0.37 to −0.42; P < 0.005) and two at the end of study (AHEI 2010 & AHEI-P 2010 r = −0.39, −0.30, respectively, P < 0.040). Changes in diet quality and %HPF were not related ( P > 0.05). Conclusions: Interventions aimed to prevent excessive gestational weight gain showed improvements in diet quality. Hyper-palatable food consumption was negatively related to diet quality, yet neither intervention decreased %HPF. Focusing on increasing dietary fiber may allow for a targeted message with broad implications for diet quality, but more research is needed. Funding Sources: NIH Clinical and Translational Science Award and the Kansas City Area Life Science Institute.